Connectome-based predictive modeling of grip strength: a marker of physical frailty - Ghaffari, Amin; Abouzaki, Majd; Romero, Yasmine; Sun, Andrew; Seitz, Aaron; Langley, Jason; Bennett, Ilana J.; Hu, Xiaoping (Frontiers in Neuroscience, 2025)
IntroductionFrailty is characterized by a persistent and progressive decline in functional capacity, leading to increased vulnerability to stressors and a heightened risk of adverse health outcomes, both physically and mentally. Despite frailty’s prevalence in older adults, there is limited research on its neural substrates.MethodsIn this study, we used connectome-based predictive modeling (CPM) to find a linear relationship between task-based connectomes taken from tasks that involved similar handgrip manipulations and a separate measure of physical frailty: the maximum grip strength in older adults.ResultsWe observed that the task-based connectomes were able to explain individual differences in grip strength, with the Subcortical and Cerebellum network, particularly the caudate nucleus functional connectivity, being the strongest predictor.DiscussionThese findings demonstrate that task-based functional connectomes can serve as personalized markers for predicting individual behavioral measures, such as handgrip strength, and highlight the role of the caudate nucleus in physical frailty.